Catalyst-free, microdroplet-mediated waste plastic conversion to diacids - Ruiliang Gao; Liwei Zhang; Richard J. Lewis; Hao Wang; Zhiyan Pan; Yage Zhang; Zekai Yu; Zhiqiang Liu; Xiaolin Guo; Xiangbowen Du; Wencong Liu; Minghang Li; et al. (Nature, 2026)
Abstract Plastic waste accumulation poses a global threat to both the environment and public health 1–3 . Although catalytic upcycling to value-added chemicals holds promise, its industrial adoption is hindered by additive-induced catalyst deactivation, feedstock heterogeneity, process inflexibility and limited economic viability 4 . Here we report a catalyst-free upcycling strategy that makes use of in situ generation of hydroxyl radicals at microdroplet interfaces 5–8 to enable oxidative cleavage of diverse waste plastics—from polyolefins to rubbers—into carboxylic acids under mild conditions. By eliminating catalyst-dependent pathways, this approach circumvents key challenges of catalyst design and poisoning, while substantially lowering technical barriers and costs 9,10 . Our method achieves complete conversion of polyethylene (PE) with selectivity to short-chain diacids approaching 69% under relatively mild conditions and demonstrated broad applicability to mixed commercial plastics, with scalability demonstrated up to the 300-g scale. Radical intermediate analysis reveals the crucial role of H 2 O in mediating a unique oxidative degradation mechanism: sequential hydroxyl radical addition to alkyl radicals, distinct from classical liquid-phase aerobic oxidation of alkane 11 . This interfacial radical-mediated strategy enables sustainable polymer upcycling with minimal infrastructure. More broadly, this work provides a scalable blueprint for the first, to our knowledge, industrial implementation of microdroplet chemistry, with transformative implications for oxidation processes in organic acid synthesis and beyond.